2021
DOI: 10.1215/00703370-9305166
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Rental Assistance for Children's Health and School Attendance in the United States

Abstract: Programs that provide affordable and stable housing may contribute to better child health and thus to fewer missed days of school. Drawing on a unique linkage of survey and administrative data, we use a quasi-experimental approach to examine the impact of rental assistance programs on missed days of school due to illness. We compare missed school days due to illness among children receiving rental assistance with those who will enter assistance within two years of their interview, the average length of waitlis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…2021; Fenelon et al. 2018, 2021). Others have found that children growing up in public housing have better educational outcomes and better economic outcomes in adulthood (Currie and Yelowitz 2000; Newman and Harkness 2002; Newman and Holupka 2021; Schwartz et al.…”
Section: Empirical Evidence For 2gen Spillovers and Multipliersmentioning
confidence: 99%
“…2021; Fenelon et al. 2018, 2021). Others have found that children growing up in public housing have better educational outcomes and better economic outcomes in adulthood (Currie and Yelowitz 2000; Newman and Harkness 2002; Newman and Holupka 2021; Schwartz et al.…”
Section: Empirical Evidence For 2gen Spillovers and Multipliersmentioning
confidence: 99%
“…As such, shared alliances are necessary to address multilayered characteristics and can include collaborations among agencies (e.g., education, housing, legal, public health, welfare) to better track students removed from the educational process and to develop comprehensive early warning and intervention systems salient to a particular area. An example involves multiagency collaboration in areas of housing instability and residential mobility to facilitate rental assistance and transportation to a previous school for vulnerable students (Fenelon et al, 2021). Kearney and Graczyk (2020) noted as well that the very nature of a school's purpose must change in MD-MTSS frameworks of school attendance/problems in areas of high absenteeism severity.…”
Section: Tiermentioning
confidence: 99%
“…( National Academies of Sciences E, and Medicine, 2019, and Medicine, 2019 ) Multiple studies using quasi-experimental designs have demonstrated the impacts of enrollment in a single program, such as the Supplemental Nutrition Assistance Program (SNAP) or federal rental assistance, on health, social, and economic outcomes including adult earnings, asthma risk, school absenteeism, and mental health. ( Hoynes et al, 2016 , Fenelon et al, 2021 , Fenelon et al, 2017 , Boudreaux et al, 2020 , Denary et al, 2021 ) Moreover, as concluded through simulation modeling by the National Academies of Sciences, Engineering, and Medicine, concurrent enrollment in multiple safety net programs may have even greater impacts due to synergies between health and economic benefits. ( National Academies of Sciences E, and Medicine, 2019 ) For example, a pre/post study in the San Francisco Bay area found receipt of both SNAP and Supplement Security Income (SSI) improved household food security and self-rated health and reduced psychological distress compared to only receiving SSI.…”
Section: Introductionmentioning
confidence: 99%